Analisis Tekstual Dan Kontekstual Tari Batobo Di Kanagarian Piobang Kecamatan Payakumbuh Kabupaten 50 Kota - Sisi Ranita Yahya; Nerosti Nerosti (Jurnal Kajian dan Penelitian Umum, 2023)
This study aims to describe and analyze the textual and contextual analysis of Batobo Dance in Kanagarian Piobang, Payakumbuh District, 50 City Regency. This type of research is qualitative research with descriptive methods of analysis. This research instrument is the researcher himself and is assisted by supporting instruments such as stationery and cameras. Data were collected through literature study, observation, interviews and documentation. The steps of analyzing data are collecting data, describing the data and inferring the data. The results showed that Batobo Dance was analyzed based on textual and contextual analysis. The textual analysis of Batobo Dance is to describe batobo activities clearly and each community has a role in batobo. Male dancers do the work of hoeing the rice fields while female dancers do the movement of catching fish at times on the edge of the rice fields, also do planting movements, to rice manuai. While the contextual analysis of this dance has reflected a compact life in society, the spirit of gotong royong is strongly reflected in the energetic and happy movements of dancers. This activity is driven by niniak mamak, this activity basically aims to foster children and nieces and nephews in achieving unity and unity for common life, especially in cultivating rice fields or fields.